The positive effect of explicit positive evidence. Issue 2 (9th October 2018) - Brandel, Noa
Abstract : The study investigates questions central to the field of second language (L2) acquisition and instruction: Does the first language (L1) influence the L2 grammar? Can wrong patterns be restructured? Is Universal Grammar accessible during L2 acquisition? And can L2 acquisition, rather than learning (in Krashen's sense), be triggered by explicit positive evidence (EPE), combining input flood with explicit emphasis upon target forms? Three properties associated with the Null Subject Parameter were inspected in two sixth-grade groups (L1-Hebrew, L2-English): thematic subject omission, expletive subject omission, and post-verbal subjects. During teaching, both groups were exposed to input flood of expletive subjects, but only in one group were expletives explicitly emphasized (EPE). A Hebrew-toEnglish translation-choice task tested the abovementioned properties pre-teaching, immediately post-teaching, and four months post-teaching. Shortly after teaching, the group which was explicitly taught improved significantly in rejecting ungrammatical null expletives and post-verbal subjects, but not null thematic subjects, thus indicating (partial) clustering. However, the improvement attained was not fully preserved four months later. The results show that shortterm exposure to EPE concerning a single property can apparently trigger change in another property, suggesting that learned knowledge can affect L2 competence, and that Universal Grammar plays a role in L2 acquisition.